Multi-response evaluation of encapsulated pandan leaf powder under different drying and wall material conditions - Nitisuk, Panorjit; Wanyo, Pitchaporn; Chamsai, Tossaporn (Journal of Food Technology Research, 2025)
Pandan (Pandanus amaryllifolius) leaf extract contains high amounts of bioactive compounds; however, its stability is compromised during processing, limiting its broader use in functional foods. This study aimed to optimize encapsulation techniques to improve the physicochemical properties, bioactive retention, and functional efficacy of pandan extract powder. A 3×3 full-factorial experimental design was applied, involving three drying methods (spray-drying, freeze-drying, and drum-drying) and three wall materials (maltodextrin, soy protein isolate, and egg white powder). Several quality indicators were determined, such as moisture content, water activity, solubility, encapsulation efficiency, color properties, total chlorophyll, and β-carotene, as well as antioxidant activity (DPPH, FRAP, and ABTS assays). Results demonstrated that freeze-drying combined with soy protein isolate produced powders with the highest encapsulation efficiency (76.42%), accompanied by antioxidant activity (FRAP: 64.53 µM FeSO₄/g; ABTS: 88.81%) and a low water activity (0.337), showing improved stability. Spray-drying using egg white powder provided excellent solubility and a high level of encapsulation efficiency. Drum-drying proved to be the least effective procedure. Multi-response optimization was performed by principal component analysis (PCA) combined with the desirability function, which revealed the optimum condition of freeze-drying using soy protein isolate. These findings provide a valuable decision-making framework for selecting drying techniques and wall materials to develop high-quality, shelf-stable, and antioxidant-rich functional powders. The practical implication of this study is its potential to guide the food and nutraceutical industries in producing standardized pandan-based products with enhanced bioefficacy and market potential.